Navigating Uncharted Territory: A post Covid-19 Exploration of the Resilience of Women Owned Small Businesses in the Wake of the Pandemic - Gift Donga; Tendai Chimucheka (Research Synergy Foundation, 2024)
Resilience has long been acknowledged in the literature as a crucial aspect of the entrepreneur's character and personality. Additionally, it is acknowledged as a vital component of the entrepreneurial process that propels businesses to great outcomes. However, to the researchers’ knowledge, there remains limited understanding regarding how women-owned small businesses in South Africa withstand and function during challenging social and economic crises like the COVID-19 pandemic. In the post-modern period we live in today, women will inevitably play an important part in business and economic development, and they are eager to become involved and make a difference in their communities. The COVID-19 pandemic has intensified the challenges faced by female entrepreneurs in growing their businesses. This research focuses on investigating how resilient South African women entrepreneurs have been in response to the pandemic. Drawing from resilience theory, the study employed a qualitative approach to gather and analyze data from a group of 15 women entrepreneurs based in the Eastern Cape Province of South Africa, using thematic analysis. The following four themes emerged from the findings; business agility; optimistic outlook; leveraged digital technology; and business networks. This research enhances existing resilience theory by integrating fresh insights gathered from the resilience strategies employed by female entrepreneurs in times of crisis. Results from the study are also expected to contribute to sustaining South African women owned small businesses and empowering their resilience, despite adversities.